1991
DOI: 10.1002/hep.1840130113
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell activation and endothelial cell damage after storage of rat livers: Effects of reperfusion

Abstract: Reperfusion injury characterized by loss of endothelial cell viability occurs after cold ischemic storage of livers for transplantation surgery. Here, ultrastructural changes in stored rat livers were examined by scanning and transmission electron microscopy. With increasing times of storage in Euro-Collins solution (4 to 24 hr) followed by 15 min of reperfusion at 37 degrees C, a sequence of structural alterations was observed involving endothelial and Kupffer cells. Widening of endothelial fenestrations occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
138
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 26 publications
11
138
1
2
Order By: Relevance
“…Conversely, subsequent warm culture, which mimicks warm reperfusion, induced a further 15% to 20% loss of cell viability at all preservation times. These two stages of cytotoxicity correspond to the results obtained for nonparenchymal cells in the isolated perfused rat liver 7 and reflects the two major stages of transplantation injury in humans. 1 In the present study, we have found that cold storage in SLS solution affords as good a preservation of gross cell viability as does UW solution, whether during simple cold storage or after rewarming.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Conversely, subsequent warm culture, which mimicks warm reperfusion, induced a further 15% to 20% loss of cell viability at all preservation times. These two stages of cytotoxicity correspond to the results obtained for nonparenchymal cells in the isolated perfused rat liver 7 and reflects the two major stages of transplantation injury in humans. 1 In the present study, we have found that cold storage in SLS solution affords as good a preservation of gross cell viability as does UW solution, whether during simple cold storage or after rewarming.…”
Section: Discussionsupporting
confidence: 85%
“…5,6 Unlike other organs, transplantation injury in the liver is characterized by microcirculatory problems that are related mainly to the sensitivity of liver endothelial cells to cold preservation and rewarming. 1,5,7 Morphologically, they show retraction of cytoplasm (rounding up) during cold preservation that progresses toward loss of viability and denudation of the sinusoids after warm reperfusion. 7 Although hepatocytes appear to be the most resistant cell type to cold storage and rewarming according to morphological studies, 7 others, including our-selves, have shown that their metabolic and transport functions are perturbed.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, liver nonparenchymal cells, including tissue macrophages (Kupffer cells) and the sinusoidal endothelium, are sensitive to cold ischemia. 2,32 Although the cold ischemic time was short (median, 5 hours), active HMGB1 secretion during graft procurement and preservation may partly account for hepatic HMGB1 outflow during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence indicates that KC (the resident macrophages of the liver) may cause hepatic injury in various disease processes, including cold [54] and warm [55] ischemic injury. Ischemia activates KC, which are the main source of ROS during the reperfusion period [53].…”
Section: Ischemia/reperfusion Liver Injury and Free Radicalsmentioning
confidence: 99%